A Prospective Crossover Comparison Study of the Single-Needle and Multiple-Needle Techniques for Facet-Joint Medial Branch Block. Issue 5 (1st September 2005) - Stojanovic, Milan P.; Dey, Dennis; Hord, E. Daniela; Zhou, Yili; Cohen, Steven P.
Abstract : Background and Objectives: Medial branch blocks have been widely described in the literature as a diagnostic tool for facet joint pain. Recently, a new "single-needle' technique was described that is purported to be equally accurate, and in some respects, superior to the standard multiple-needle technique. To date, no studies have been performed that compared these 2 techniques. Methods: In a multicenter setting, 24 subjects underwent 2 separate diagnostic medial-branch blocks in a randomized, single-blind crossover comparison of the single-needle and multiple-needle techniques. Multiple variables were compared between the 2 techniques, including procedure-related discomfort, postprocedure pain relief, volume of local anesthetic required, accuracy as determined by final needle position and contrast-media spread, and time needed to perform the procedure. Results: In this pilot study, the single-needle technique resulted in less procedure-related pain ( P = .0003), required less superficial local anesthesia ( P =.0006), and took less time to complete ( P < .0001) than did the multiple-needle approach. With regard to final needle position, contrast spread, and postprocedure pain relief ( P = .8), no differences were noted between the 2 techniques. Conclusions: Our results indicate that the single-needle technique takes less time to perform and causes less patient discomfort than does the standard technique but provides the same degree of accuracy. More studies with larger sample sizes are needed to corroborate these results and explore the effect the single-needle approach has on the rate of false-positive medial branch blocks.